2012
DOI: 10.1021/ja311821h
|View full text |Cite
|
Sign up to set email alerts
|

Bromine Radical-Mediated Sequential Radical Rearrangement and Addition Reaction of Alkylidenecyclopropanes

Abstract: Bromine radical-mediated cyclopropylcarbinyl-homoallyl rearrangement of alkylidenecyclopropanes was effectively accomplished by C-C bond formation with allylic bromides, which led to the syntheses of 2-bromo-1,6-dienes. A three-component coupling reaction comprising alkylidenecyclopropanes, allylic bromides, and carbon monoxide also proceeded well to give 2-bromo-1,7-dien-5-ones in good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 49 publications
(12 reference statements)
1
31
0
Order By: Relevance
“…Dichloromethane and hexane were distilled from P 2 O 5 . Cyclopropylidenealkanes 1a – i were prepared by Wittig olefination reactions of the corresponding aldehydes and ketones upon treatment with 3‐bromopropyltriphenylphosphonium bromide and t BuOK . Cyclobutylidenealkanes 7a , 7c , 7h , 7i were prepared in an analogous manner from the corresponding ketones, 4‐bromobutyltriphenylphosphonium bromide and t BuOK.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichloromethane and hexane were distilled from P 2 O 5 . Cyclopropylidenealkanes 1a – i were prepared by Wittig olefination reactions of the corresponding aldehydes and ketones upon treatment with 3‐bromopropyltriphenylphosphonium bromide and t BuOK . Cyclobutylidenealkanes 7a , 7c , 7h , 7i were prepared in an analogous manner from the corresponding ketones, 4‐bromobutyltriphenylphosphonium bromide and t BuOK.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclopropylidenealkanes 1a-i were prepared by Wittig olefination reactions of the corresponding aldehydes and ketones upon treatment with 3-bromopropyltriphenylphosphonium bromide and tBuOK. [43] Cyclobutylidenealkanes 7a, 7c, 7h, 7i were prepared in an analogous manner from the corresponding ketones, 4-bromobutyltriphenylphosphonium bromide and tBuOK. 1,1′-Bi(cyclobutylidene) (7j) was prepared from 3-bromopropyltriphenylphosphonium bromide and tBuOK in 50 % yield.…”
Section: Methodsmentioning
confidence: 99%
“…Radical addition of an allyl moiety and a bromine atom across the π-system of alkenes and allenes has been developed recently [74]. When applied to alkylidenecyclopropanes (e.g., 113) in the presence of CO, a polyfunctional substrate 115 is obtained with high efficiency (Scheme 14.25) [75]. The reaction proceeds through the addition of the Br radical on the central atom of the alkylidenecyclopropane to produce a cyclopropylmethyl radical that rearranges into a homoallylic radical.…”
Section: Miscellaneous Carbonylation Reactionsmentioning
confidence: 99%
“…The resultsa re summarized in Ta ble 1. Afterwards, an optimizationo fs everal additives, including NEt 3 ,N aHCO 3 ,N a 2 CO 3 , K 2 CO 3 ,K 2 HPO 4 ,a nd 1,8-diazabicyclo [5.4.0]undec-7-ene( DBU), revealed that product 3a could be obtained in the highest yield when the reaction was conducted in the presence of DBU (Table 1, entries [14][15][16][17][18][19]. We next screened different photocatalysts, such as Ir(ppy) 3 ,R u(bpy) 3 Cl 2 , [Ru(bpy) 3 ](PF 6 ) 2 ,I r 2 (bpy) 4 Cl 2 ,R u(phen) 3 Cl 2 ,a nd Ru(bpy) 3 Cl 2 ·6 H 2 O ( Table 1, entries 2-7).…”
mentioning
confidence: 99%
“…The solvent screening showedt hat polar solvents were beneficial to this reaction;e mploying DMFa st he solvent, the reactiong ave the best result. Afterwards, an optimizationo fs everal additives, including NEt 3 ,N aHCO 3 ,N a 2 CO 3 , K 2 CO 3 ,K 2 HPO 4 ,a nd 1,8-diazabicyclo [5.4.0]undec-7-ene( DBU), revealed that product 3a could be obtained in the highest yield when the reaction was conducted in the presence of DBU ( Table 1, entries [14][15][16][17][18][19]. Moreover,w et ried to use am ixture of DBU and K 2 CO 3 as base or increaset he amount of 2 to 2.5 equivalents, neither of which affected the yield significantly (Table 1, entries 20-21).…”
mentioning
confidence: 99%